Pengaruh Model Pembelajaran 3cm dalam Meningkatkan Keterampilan Berpikir Kreatif Siswa pada Mata Pelajaran IPA - Novi Alpani Nurajijjah; Titim Fatimah; Inne Martthyane Pratiwi (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
This research is motivated by the low creative thinking skills of students in the science subject. An alternative to improving students' low creative thinking skills is by implementing the 3CM (Cool, Critical, Creative, Meaningful) learning model. This study aims to determine the difference in the average increase in creative thinking skills of fifth-grade students in science subjects using the 3CM (Cool, Critical, Creative, Meaningful) learning model compared to students using the problem-based learning model. The population of this research includes all fifth-grade students at MIN 2 Kota Bandung for the 2023/2024 academic year. The samples taken are class V-A and class V-B. The data collection techniques used are tests and observations. Data analysis techniques include normality tests, homogeneity tests, and independent t-tests. The independent t-test results on the N-gain data showed a significance value of 0.003, indicating a difference in the average increase in creative thinking skills in science subjects. The 3CM learning model has a learning syntax that includes: providing motivation, interpreting contextual problems, criticizing contextual issues, resolving conflicts, converting concepts into creative products, confirming creative products, and reflecting meaningfully.